Proceso de ASC - EL IMPACTO DE LA PARTICIPACION CIUDADANA, MEDIANTE AUDIENCIAS PUBLICAS, EN LAS DECISIONES DE LA CORTE CONSTITUCIONAL COLOMBIANA. 1996 - 2018 (2020)
This small research project seeks to analyze the incidence of citizen participation through public hearings in the decisions made by the Colombian Constitutional Court (hereinafter CCC) between 1996 and 2018. Research on this topic is justified given that citizen participation in the judiciary is a response to the dilemma between constitutionalism and democracy, which, however, has been little explored from the empirical point of view in Colombia